So close and yet so far: The ability of mandatory disclosure rules to crack down on offshore tax evasion - Elisa Casi-Eberhard; Mohammed Mardan; Rohit Reddy Muddasani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We study the short-term effect of the introduction of the mandatory disclosure programme for aggressive tax arrangements by focusing on the one introduced in May 2018 under Council Directive 2018/288/EU (or DAC6). Employing bilateral data on cross-border deposits, we study the effect of this new disclosure requirement on cross-border tax evasion. Our results show a reduction of cross-border deposits in EU countries with strong enforcement, captured by large monetary penalties for misreporting. At the same time, we document a relocation of income and wealth to countries with limited intermediary reporting obligations. Finally, we detect a shortterm increase of US14 billion in cross-border deposits held in countries offering citizenship/residence by investment programmes, suggesting the use of these schemes as regulatory arbitrage to circumvent the disclosure mandated under DAC6. We provide timely and relevant evidence contributing to the debate on international administrative cooperation to reduce cross-border tax evasion.
Keywords: H26; G21; F42; 330; tax evasion; intermediary reporting; administrative cooperation; cross-border deposits